2010
DOI: 10.1088/0268-1242/25/4/045024
|View full text |Cite
|
Sign up to set email alerts
|

Mobility limiting scattering mechanisms in nitride-based two-dimensional heterostructures with the InGaN channel

Abstract: The scattering mechanisms limiting the carrier mobility in AlInN/AlN/InGaN/GaN twodimensional electron gas (2DEG) heterostructures were investigated and compared with devices without InGaN channel. Although it is expected that InGaN will lead to relatively higher electron mobilities than GaN, Hall mobilities were measured to be much lower for samples with InGaN channels as compared to GaN. To investigate these observations the major scattering processes including acoustic and optical phonons, ionized impurity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 31 publications
(53 reference statements)
0
18
2
Order By: Relevance
“…The IFR has been treated as a combined scattering mechanism which includes effects of all interfaces. The strong effect of IFR can be attributed to the InGaN layer's growth quality, which is also consistent with the literature 15–17.…”
Section: Resultsmentioning
confidence: 99%
“…The IFR has been treated as a combined scattering mechanism which includes effects of all interfaces. The strong effect of IFR can be attributed to the InGaN layer's growth quality, which is also consistent with the literature 15–17.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of some minor deviations that can be related to experimental uncertainties, the proposed model is able to match the available experimental results well. Being generic in nature, this model also applies to InAlN/InGaN/GaN heterostructure designs [36][37][38][39]. This is because the surface state parameters of an InAlN barrier layer is already available [40].…”
Section: Thin Conducting Layer: D Ingan D Thinganmentioning
confidence: 99%
“…Several attempts have also been made to elucidate the transport mechanisms in InGaN channel HFETs. Gökden investigated the carrier mobility in AlInN/AlN/InGaN/GaN heterostructures and compared with devices without InGaN channel. The results revealed that the main scattering limits the electron mobility at low and intermediate temperature is interface roughness for heterostructures having InGaN channels.…”
Section: Introductionmentioning
confidence: 99%